Molecular Design of Interfaces of Model Food Nanoemulsions: A Combined Experimental and Theoretical Approach - Tamara Martínez-Senra; Sonia Losada-Barreiro; Jose M. Hermida-Ramón; Ana M. Graña; Carlos Bravo-Díaz (MDPI AG, 2023)
The composition and structure of the interfacial region of emulsions frequently determine its functionality and practical applications. In this work, we have integrated theory and experiments to enable a detailed description of the location and orientation of antioxidants in the interfacial region of olive-oil-in-water nanoemulsions (O/W) loaded with the model gallic acid (GA) antioxidant. For the purpose, we determined the distribution of GA in the intact emulsions by employing the well-developed pseudophase kinetic model, as well as their oxidative stability. We also determined, by employing an in silico design, the radial distribution functions of GA to gain insights on its insertion depth and on its orientation in the interfacial region. Both theoretical and experimental methods provide comparable and complementary results, indicating that most GA is located in the interfacial region (~81.2%) with a small fraction in the aqueous (~18.82%). Thus, GA is an effective antioxidant to inhibit lipid oxidation in emulsions not only because of the energy required for its reaction with peroxyl radical is much lower than that between the peroxyl radical and the unsaturated lipid but also because its effective concentration in the interfacial region is much higher than the stoichiometric concentration. The results demonstrate that the hybrid approach of experiments and simulations constitutes a complementary and useful pathway to design new, tailored, functionalized emulsions to minimize lipid oxidation.